EFEKTIVITAS PLATFORM PEMBELAJARAN MATEMATIKA BERBASIS DIGITAL UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA SEKOLAH DASAR - Ratri Nuryani Qudwatullathifah; Zakiyah Ismuwardani; Mochamad Guntur; Siti Musyarrofah; Nur Indah Septia Ningsih (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
The lack of use of digital platforms as a learning tool at the elementary school level is one of the causes of low student learning outcomes in solving mathematical problems. This study uses a quantitative approach. The aim of the research is to improve elementary school students' problem-solving abilities with a digital-based platform in the form of live worksheets. The research population consisted of 300 students enrolled in a school. The data collection technique was a random sample (random sampling) of 49 students. The test instruments used are in the form of pretest and posttest sheets. The results showed that the pretest average was 21.24, the lowest score obtained on the pretest was 10, while the highest score was 25. Meanwhile, the average posttest score was also 21.24, the lowest score on the posttest was also 10, while the highest score was 25. It can be concluded that the average pretest and posttest scores are the same, namely 21.24. In addition, the range of scores from the lowest score to the highest score is from 10 to 25, indicating that there is variation in student performance but not too extreme. This concludes that the use of a digital platform in the form of live worksheets can improve students' problem solving abilities in mathematics learning.